An analysis of the types of figurative languages found in “the adventures of tom sawyer” novel by mark twain - Wahyuni, Ni Komang Dila Candra; Utami, Ni Made Verayanti; Ariyaningsih, Ni Nyoman Deni (Institut Pariwisata dan Bisnis Internasional, 2020)
The purpose of this study is to find out the types of figurative language in the novel entitled “The Adventures of Tom Sawyer”. This study used descriptive qualitative method. The data were analyzed based on the theory of Perrine (1977) about the twelve types of figurative language. The result of this analysis showed that there were 11 types of figurative languages found in this novel are; simile, personification, metaphor, synecdoche, allegory, paradox, metonymy, hyperbole, symbol, understatement, and irony. The type of figurative language that does not existed in this novel is the apostrophe. The types of figurative language personification and hyperbole are dominantly used in this novel, the author wants to make the reader not bored reading the novel and to make the readers know clearly the character of the existing characters in the novel. By using hyperbole readers can clarify the character or personality of the characters. The researcher proposed suggestions for the readers and literary enthusiasts are able to understand the study of figurative language in particular use of language as a tool for communication.